6x+7=-2x-33

Simple and best practice solution for 6x+7=-2x-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7=-2x-33 equation:


x in (-oo:+oo)

6*x+7 = -2*x-33 // + -2*x-33

6*x-(-2*x)+7+33 = 0

6*x+2*x+7+33 = 0

8*x+40 = 0 // - 40

8*x = -40 // : 8

x = -40/8

x = -5

x = -5

See similar equations:

| 1+2d=6d+49 | | 2y+x=2y-8 | | 3x-7=56-6x | | -9-4d=d-29 | | -7b+4=-b-68 | | x-10=-7x+46 | | 7d+1=4d+34 | | -6-5x=-x-30 | | -1+x=-4x-56 | | 3a-4=68-6a | | -5-k=6k-40 | | c+54=6 | | -2d-9=-27+4d | | 3b-10=-b-6 | | 2t-1=-25-2t | | 5-3w=-5w-19 | | 2n+7=3n+9 | | y=-6+21 | | -6+7a=3a-54 | | 2m-5=3m-12 | | b+8=7b+32 | | -4+w=4w-37 | | x^2-9x-190=0 | | 6y^2-5y-1= | | 3+12s-1=5s+92-3s | | 2(x+3)-3(2x-9)= | | 10n-6=9n+2 | | 32b+21= | | -7+6n=3n+5 | | -4-d=2d-40 | | 3-2b=2b-17 | | 8+7a=-3a+108 |

Equations solver categories